Chad : Requests for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Additional Interim Assistance Under the Enhanced HIPC Initiative. (IMF Staff Country Reports; Country Report ;, 2005)
This paper analyzes requests from Chad authorities for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF) and Additional Interim Assistance Under the Enhanced Heavily Indebted Poor Countries (HIPC) Initiative. The authorities made progress in implementing structural reforms in 2004. In particular, they took corrective measures for the two structural benchmarks missed under the sixth review of the previous PRGF arrangement. They also continued efforts to meet structural conditions for the completion point under the enhanced HIPC Initiative.